Current Problems of Codification of Innovations in Forensic Practice in the Russian Federation - S. A. Smirnova; G. G. Omel'yanyuk; A. I. Usov (Теория и практика судебной экспертизы, 2016)
The paper addresses key innovations brought forward by the draft federal law “On forensic science services in the Russian Federation”, e.g. validation of methodological documentation on forensic operations, certification of the competence of forensic examiners, certification of methodological support for forensic operations, standardization of forensic practices, as well as the record of the practical application of these innovations in the operations of the RFCFS of the Ministry of Justice of the Russian Federation.